Structural, Electrical and Magnetic Properties of Mechanothermally Synthesized Bi (Co0.45Ti0.45Fe0.10)O3 Nanoceramic. Issue 1 (March 2020) - Kumar, Nripesh; Shukla, Alok; Kumar, Nitin
Abstract: High-energy ball mill was exploited to synthesize Bi(Co0.45 Ti0.45 Fe0.10 )O3 nanoceramic, followed by solid-state cramicmethod. XRD (X-ray diffraction), SEM (scanning electron microscopy) and impedance spectroscopy methods were exploited to analyze elementary crystal structure, micrograph and comprehensive electrical characteristics of the as -synthesized nanoceramic. The impedance spectroscopy technique offered many exciting outcomes on the influenceof grain and grain boundary on the total resistiveproperties of the nanoceramic. The trend of frequency dependence of a.c. conductivity follows Jonscher's power law. The upgraded conductivity and dielectric property propose various applications in the embedded capacitors. PE loop tracer and VSM (Vibrating sample Magnetometer) were exploited to study the ferroelectric and magnetic characteristics of the synthesized nanoceramic. The B-site modified BiFeO3 (with Co and Ti) exhibit ferroelectric and magnetic behavior at room temperature.